Energy security: Demands imposed on German and European foreign policy by a changed configuration in the world energy market - Friedemann Müller (Stiftung Wissenschaft und Politik (SWP), 2007)
Several developments cause concern about the security of Europe's energy supply: (1) Russia's policies towards countries through which its oil and natural gas transit; (2) Venezuela's and Iran's threats to instrumentalize Western import dependence for political ends; (3) Saudi Arabia's non-transparent oil policy; and (4) persistent insecurity in Iraq. These developments also indicate an increasingly dysfunctional world market.On the supply side, the market does not function due to the rapid decline in oil and gas reserves in countries that follow rules of a competitive market and a resulting concentration of world reserves in countries that do not. This dysfunction has resulted in an oil price at least ten times above marginal production costs in the Middle East. After their nationalization, the behavior of oil companies in the Middle East, Venezuela, and Russia becomes far less predictable than that of a profit-seeking company in a competitive market.On the demand side, shares in the world market are shifting from OECD countries to emerging countries such as China, India, and South-East Asian states. Chinese state-owned companies are behaving like monopolists with a political agenda and state backing in Sudan, Nigeria, and Iran. Emerging Asian countries will likely motorise in the 21st century the way Western countries motorised in the 20th. Even under free market conditions, producers will hardly be able to provide sufficient oil-based fuels to supply the three billion potential car drivers in these countries.To establish rules for the relationship between established and emerging consumers and between consumers and producers won't do. A supplementing strategy to end the oil age in the coming decades is needed, with Western states taking the lead due to the greater technological options available to them as to emerging economies. (SWP Research Papers)
Keywords: 320